Clustering of adolescent health concerns: A latent class analysis of school students in New Zealand. Issue 11 (20th November 2013) - Noel, Hannah; Denny, Simon; Farrant, Bridget; Rossen, Fiona; Teevale, Tasileta; Clark, Terryann; Fleming, Terry; Bullen, Pat; Sheridan, Janie; Fortune, Sarah
Abstract : Aims: The aims of this study are to identify clinically meaningful groups of adolescents based on their engagement in high levels of risk behaviours or severe emotional health concerns and to describe the demographic characteristics of these groups in two populations of school students in New Zealand. Methods: A nationally representative sample of secondary school students was surveyed in 2007; alternative education (AE) students in Auckland and Northland were surveyed in 2009. A total of 9107 secondary school students and 335 AE students completed a youth health questionnaire using Internet tablets. Latent class analysis (LCA) was used to identify groups of students on the basis of distinct profiles of their risk behaviours and mental health concerns. Results: The majority (80%) of students in secondary schools are 'healthy' and report few health concerns, 16% are considered 'risky' or 'distressed', and 4% report 'multiple' risk behaviour profiles or emotional health concerns. In AE, only 21% of students were considered 'healthy' with most featuring in the 'risky' or 'multiple' groups. Females were more likely to be 'distressed', whereas males were more likely to feature in the 'risky' or 'multiple' groups. Conclusions: Clinically‐concerning health risk behaviours and emotional health concerns 'cluster' in up to 20% of students in secondary schools and up to 79% of students in AE. Gender, ethnic and socio‐economic disparities are also observed. This highlights the importance of comprehensive psychosocial assessment and appropriate service provision, particularly for at‐risk groups.